2018
DOI: 10.4269/ajtmh.17-0770
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Typhoid Fever and Spotted Fever Group Rickettsiosis Presenting Concomitantly in an Indian Immigrant

Abstract: We present a rare case of an Indian immigrant suffering from concomitant infection of and spotted fever group. We discuss the scarce reports of dual infections from the developing world and the related diagnostic challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In almost 306 cases, diagnostic samples consisted of blood [ 63 ]; occasionally, other samples alone or in conjunction with blood have been used, such as eschar swab [ 64 ], skin biopsy [ 65 ], vesicles swab [ 66 ], CSF [ 67 ], central nervous system biopsy (autoptic) [ 56 ], pleural fluid [ 68 ], liver biopsy [ 62 ] and in vectors found feeding on patients [ 69 ]. On 22 occasions, an infected tick was found while biting the patient’s skin [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In almost 306 cases, diagnostic samples consisted of blood [ 63 ]; occasionally, other samples alone or in conjunction with blood have been used, such as eschar swab [ 64 ], skin biopsy [ 65 ], vesicles swab [ 66 ], CSF [ 67 ], central nervous system biopsy (autoptic) [ 56 ], pleural fluid [ 68 ], liver biopsy [ 62 ] and in vectors found feeding on patients [ 69 ]. On 22 occasions, an infected tick was found while biting the patient’s skin [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Israelensis was diagnosed using the molecular method/PCR on an Indian traveler in Israel [ 58 ]. Another case of SFG rickettsiosis /typhoid co-infection was reported in Israel from an Indian traveler in 2018 [ 59 ]. A case of novel SFG Candidatus R. indica Tenjiku01 was reported in Japan from a traveler returning from Karnataka [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In India, concomitant infection of Salmonella and Rickettsia have been reported in some recent studies. 16 Cohen et al reported one such dual infected case and suggested that the dual infection must be considered in post-travel patients and in immigrants from developing countries. Seow et al from Singapore also reported Typhoid and Scrub Typhus Coinfection in one India Returned Traveler.…”
Section: Studies By Lin Et Al Suggested Crp [C Reactive Protein]mentioning
confidence: 99%